Scindapsus scortechinii Hook. f. (Araceae) - A new angiospermic record for Bangladesh - Ara, Hosne; Partha, Pavel; Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2004)
No abstract available. Bangladesh J. Plant Taxon. 11(1): 91-94, 2004 (June)